2019
DOI: 10.1152/ajpcell.00343.2018
|View full text |Cite
|
Sign up to set email alerts
|

Robust intrinsic differences in mitochondrial respiration and H2O2 emission between L6 and C2C12 cells

Abstract: Rat L6 and mouse C2C12 cell lines are commonly used to investigate myocellular metabolism. Mitochondrial characteristics of these cell lines remain poorly understood despite mitochondria being implicated in the development of various metabolic diseases. To address this need, we performed high-resolution respirometry to determine rates of oxygen consumption and H2O2 emission in suspended myoblasts during multiple substrate-uncoupler-inhibitor titration protocols. The capacity for oxidative phosphorylation suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Thus, C2C12 myotubes may have a more oxidative metabolism than L6 myotubes. This hypothesis has been confirmed in a recent study in which it was demonstrated that L6 cells had lower mitochondrial and fatty acid oxidation capacities than C2C12 cells while having higher emission of ROS ( Robinson et al. 2019 ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, C2C12 myotubes may have a more oxidative metabolism than L6 myotubes. This hypothesis has been confirmed in a recent study in which it was demonstrated that L6 cells had lower mitochondrial and fatty acid oxidation capacities than C2C12 cells while having higher emission of ROS ( Robinson et al. 2019 ).…”
Section: Discussionsupporting
confidence: 54%
“…Thus, C2C12 myotubes may have a more oxidative metabolism than L6 myotubes. This hypothesis has been confirmed in a recent study in which it was demonstrated that L6 cells had lower mitochondrial and fatty acid oxidation capacities than C2C12 cells while having higher emission of ROS (Robinson et al 2019). Future studies should therefore determine whether the higher glycolytic capacity and higher ROS emission in L6 cells exposed to PCB126 may explain the fact that this muscle cell model was more sensitive to PCB126 than C2C12.…”
Section: Direct Effect Of Pcb126 On Glucose Metabolism In Muscle Cellssupporting
confidence: 56%
“…Thus, C2C12 myotubes may have a more oxidative metabolism than L6 myotubes. This hypothesis has been confirmed in a recent study in which it was demonstrated that L6 cells have lower mitochondrial and fatty acid oxidation capacities than C2C12 cells, while having higher emission of ROS (Robinson et al, 2019). Future studies should therefore determine whether the higher glycolytic capacity and higher ROS emission in L6 cells may explain the fact that this muscle cell model is more sensitive to PCB126 than C2C12 when exposed to PCB126.…”
Section: Direct Effect Of Pcb126 On Glucose Metabolism In Muscle Cellssupporting
confidence: 54%
“…One of the studies revealed that rat L6 cells had lower rate of oxygen consumption and respiration when compared to mouse C2C12 cells during the oxidative phosphorylation and noncoupled respiration. [ 27 ] The mechanisms that are associated with the intrinsic differences in mitochondrial metabolism between mouse C2C12 and rat L6 cell will require further investigation. [ 27 ] Overall, insulin‐responsive mouse C2C12 cell line is a useful model in investigation of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%